2018
DOI: 10.1098/rsos.180634
|View full text |Cite
|
Sign up to set email alerts
|

Chromium deposition and poisoning of La 2 NiO 4 cathode of solid oxide fuel cell

Abstract: Chromium deposition and poisoning of La2NiO4 cathode of solid oxide fuel cell were studied. La2NiO4 cathode showed stable performance in the presence of metallic interconnects. Comparing with the polarization resistance (Rp) of La2NiO4 cathode in the absence of metallic interconnects, Rp did not change in the presence of metallic interconnect. After electrical conductivity relaxation method, La2NiO4 with high surface oxygen diffusion coefficients working under Cr atmosphere improved the oxygen reduction kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…24,25 Because rare-earth nickelates are free of Sr and Mn, they are also considered to possess better Crpoisoning tolerance than conventional LSM or LSCF cathodes. [26][27][28][29][30] Lee et al 26 studied the Crpoisoning effect of La 2 NiO 4+d by infiltrating Cr into the symmetric cell electrode, and they reported that performance of LNO is less sensitive to Cr than LSCF although the reaction product LaCrO 3 was observed. Hou et al 29 and Lee et al 30 investigated chromium poisoning of La 2 NiO 4 and Nd 2 NiO 4+d using symmetric cells, respectively, and they showed insignificant poisoning effects on the electrode performance and microstructure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Because rare-earth nickelates are free of Sr and Mn, they are also considered to possess better Crpoisoning tolerance than conventional LSM or LSCF cathodes. [26][27][28][29][30] Lee et al 26 studied the Crpoisoning effect of La 2 NiO 4+d by infiltrating Cr into the symmetric cell electrode, and they reported that performance of LNO is less sensitive to Cr than LSCF although the reaction product LaCrO 3 was observed. Hou et al 29 and Lee et al 30 investigated chromium poisoning of La 2 NiO 4 and Nd 2 NiO 4+d using symmetric cells, respectively, and they showed insignificant poisoning effects on the electrode performance and microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…Halfcells were cathodically polarized or held under open-circuit condition, and the ohmic and polarization resistances of the electrode were periodically characterized using galvanostatic current interruption. Different from previous studies reported by other researchers, [26][27][28][29][30] in this work, anode-supported cells (ASC) with an La 2 NiO 4+d electrode were also tested with or without current load, during which voltage-current (V-I) measurements were conducted periodically. The V-I curves were analyzed using a polarization model, and the effects of chromium poisoning on different polarization resistances of LNO electrode were studied for the first time and compared with baseline LSM electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…33,[36][37][38][39][40] SOFC operation at high and medium-high temperatures is associated with processes leading to metal corrosion and oxidation; diffusion of ions from the electrode material into the electrolyte, leading to deterioration of conductivity and stability; segregation of cations on the surface of structural elements, forming new phases; degradation of the electrochemical cell; or poisoning of SOFC anodes (Cl 2 , H 2 S, CH 3 SH, COS) [41][42][43] and cathodes (SO 2 , PO 3 , CrO 3 ). [44][45][46][47] Existing problems affect the lifetime of SOFCs, which hinders their commercialization.…”
Section: Denis Osinkinmentioning
confidence: 99%
“…Hou et al [236] concluded that LNO-214 could offer a promising chromium-resistant cathode for SOFC finding little evidence of chromium poisoning over a short-term test (~20h). Generally, the performance of LNO-214 in a dry, chromium-containing atmosphere has been shown to be relatively stable but, like many of the other materials discussed thus far, the degradation becomes significantly more prevalent in humid conditions [185,237,238].…”
Section: Lno-214mentioning
confidence: 99%